2023
DOI: 10.1111/1756-185x.14705
|View full text |Cite
|
Sign up to set email alerts
|

Damage accrual in Behçet disease: Behçet's Syndrome Overall Damage Index (BODI) versus Behçet's Disease Damage Index (BDI)

Abstract: Objectives To assess the validity of Behçet's Syndrome Overall Damage Index (BODI) and Behçet's Disease Damage Index (BDI) as tools for the detection of damage accrual in Behçet's patients compared to Vasculitis Damage Index (VDI). Also, to evaluate the correlation and the interclass correlation among the 3 indices to find out their consistency. Method A prospective cohort study was carried out on 102 adult Behçet's disease (BD) patients who were diagnosed according to the International Study Group criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[5][6][7] However, the ocular and mucocutaneous systems are the most frequently affected organ systems in BD. 8 It has been reported that approximately 50%-70% of BD patients experience ocular involvement, which can manifest as either anterior or posterior uveitis, vitreous inflammation, retinal vasculitis, scleritis, or optic neuropathy. 9 The most common ocular manifestation is uveitis, characterized by recurrent episodes of intraocular inflammation often accompanied by retinal vasculitis.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] However, the ocular and mucocutaneous systems are the most frequently affected organ systems in BD. 8 It has been reported that approximately 50%-70% of BD patients experience ocular involvement, which can manifest as either anterior or posterior uveitis, vitreous inflammation, retinal vasculitis, scleritis, or optic neuropathy. 9 The most common ocular manifestation is uveitis, characterized by recurrent episodes of intraocular inflammation often accompanied by retinal vasculitis.…”
Section: Introductionmentioning
confidence: 99%